PENGARUH KARAKTERISTIK KOMITE AUDIT DAN AUDIT EKSTERNAL SEBAGAI MEKANISME PENGAWASAN PADA MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang terdaftar di BEI tahun 2012-2013) - Adila Ashari Partono; Agus Purwanto (Diponegoro Journal of Accounting, 2015)
This study aimed to analyze the influence of audit committees and external audit of the management of corporate profits . Securities and Exchange Commission issued rules to any manufacturing company to establish an audit committee . Agency problems within the company will be controlled by the audit committee and internal audit presence . It is also supported by an external audit by the accounting firm issued an audit opinion which is able to be trusted by the principal or shareholder .The sample used is secondary data from the Indonesia Stock Exchange ( BEI ) is a manufacturing company's annual report base in 2012-2013. Variable earnings management, audit committee and external audit analyzed using multiple linear regression analysis method to test hypothesis testing and statistical test statistic t F. This is because the variables are tested more than one independent variable .These results indicate that the variable external audit had significant negative effect on earnings management. While the number of audit committee, the number of audit committee meetings , the expertise finance of audit committee had no significant effect .